1981
DOI: 10.1111/j.1365-2125.1981.tb01288.x
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of metoprine, a lipid‐soluble antifolate.

Abstract: 1 Using a dihydrofolate reductase inhibition assay, we have conducted eight pharmacokinetic studies in six patients receiving metoprine. 2 The serum level v time-curve for metoprine equivalents was irregular; first-order elimination was not observed during the study period of 0-120 h. A model-independent analysis was therefore performed, employing the area under the curve during the first 120 h (AUC). 3 At an oral dose of 65 mg/M2 without leucovorin, a peak level of 0.6 ,g/ml and an AUC of 52 /kg ml-' h produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1982
1982
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 5 publications
(4 reference statements)
0
1
0
Order By: Relevance
“…However, their therapeutic application is limited due to their adverse effects. By clinical trials, it has been shown that metoprine produces cutaneous, gastrointestinal, and hematological toxicities which have been related to their antifolate activity [ 30 , 31 ]. In addition, metoprine binds to more than 87% of serum proteins and has a plasma half-life of 216 h [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, their therapeutic application is limited due to their adverse effects. By clinical trials, it has been shown that metoprine produces cutaneous, gastrointestinal, and hematological toxicities which have been related to their antifolate activity [ 30 , 31 ]. In addition, metoprine binds to more than 87% of serum proteins and has a plasma half-life of 216 h [ 32 ].…”
Section: Discussionmentioning
confidence: 99%